A siderophore-inspired two-dimensional Fe–hydroxamate metal–organic framework. Issue 10 (15th February 2023) - Tang, Wenlei; Shao, Zhen-Wu; Xiong, Li; Zhang, Zhiyuan; Tan, Kaiyuan; Feng, Xuan; Wu, Wenjing; Liu, Chong
Abstract : Inspired by siderophores, a new two-dimensional MOF with homoleptic Fe-tri(hydroxamate) nodes is reported, featuring chemical stability and electrochemical H2 O2 -sensing potentials. Abstract : Inspired by hydroxamate-based siderophores, here we report the synthesis of a novel two-dimensional (2D) Fe–hydroxamate metal–organic framework (MOF), namely SUM-31. The MOF, constructed from homoleptic Fe(hydroxamate)3 nodes and linear E -ethylenedihydroxamate linkers, features tightly-stacked 2D layers of the honeycomb topology, with interconnected channels that ensure guest transportation and metal centre accessibility. Particularly, the impressive chemical stability of SUM-31 in an aqueous environment of a wide range (1–12) of pH, and redox-active Fe centres have made the MOF a promising electrochemical sensor for H2 O2 .